2013
DOI: 10.1097/scs.0b013e3182997d52
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Tumors of the Parotid Gland in Children

Abstract: Malignant parotid gland tumors are most common in adolescents, and this subgroup has worse outcomes. The role of radiotherapy remains controversial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
29
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 15 publications
14
29
6
Order By: Relevance
“…Similar to our results, this group showed that mucoepidermoid tumors are the most common and that surgery is the most widely employed treatment technique. This group also performed incidence calculations and showed that girls, black children, and adolescents are more frequently diagnosed with malignant parotid gland tumors and that adolescents have worse outcomes than children under the age of 15 years . Although our study did not find a similar result in regard to the effect on age on survival outcomes, in agreement with our findings this group noted that the use of adjuvant radiation was an independent predictor of poor outcomes for pediatric parotid gland malignancies.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Similar to our results, this group showed that mucoepidermoid tumors are the most common and that surgery is the most widely employed treatment technique. This group also performed incidence calculations and showed that girls, black children, and adolescents are more frequently diagnosed with malignant parotid gland tumors and that adolescents have worse outcomes than children under the age of 15 years . Although our study did not find a similar result in regard to the effect on age on survival outcomes, in agreement with our findings this group noted that the use of adjuvant radiation was an independent predictor of poor outcomes for pediatric parotid gland malignancies.…”
Section: Discussionsupporting
confidence: 88%
“…Some studies have reported negative effects on bone mass and an increased risk of secondary malignancies with this therapy in children with primary salivary gland malignancies . Our study found a similar result to a prior study that noted the use of adjuvant radiation was an independent predictor of poor outcome for pediatric parotid gland malignancies, but cautioned that these survival differences between groups may have been due to selection bias of radiotherapy for more aggressive tumors …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Most affected children are older than 10 years. Overwhelmingly, the 2 most common tumor subtypes are mucoepidermoid carcinoma (49%) and acinic cell carcinoma (40%) 48 ; however, RMS of the parotid also exists (Fig. 5).…”
Section: Parotid Tumors With Secondary Temporal Bone Invasionmentioning
confidence: 99%